2015
DOI: 10.1155/2015/762178
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Treatment with Statins and Aspirin Reduces the Risk of Prostate Cancer Detection and Tumorigenic Properties in Prostate Cancer Cell Lines

Abstract: Nowadays prostate cancer is the most common solid tumor in men from industrialized countries and the second leading cause of death. At the ages when PCa is usually diagnosed, mortality related to cardiovascular morbidity is high; therefore, men at risk for PCa frequently receive chronic lipid-lowering and antiplatelet treatment. The aim of this study was to analyze how chronic treatment with statins, aspirin, and their combination influenced the risk of PCa detection. The tumorigenic properties of these treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 49 publications
(51 reference statements)
2
25
0
Order By: Relevance
“…The investigators also evaluated the in vitro effects of aspirin, simvastatin and the combination in LNCaP and PC3 cells. The combination of aspirin and simvastatin significantly reduced proliferation in both LNCaP and PC-3 cells compared to the untreated control with no comparison to either drug alone (38). The in vivo effect of the drug combination was not investigated in this study.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…The investigators also evaluated the in vitro effects of aspirin, simvastatin and the combination in LNCaP and PC3 cells. The combination of aspirin and simvastatin significantly reduced proliferation in both LNCaP and PC-3 cells compared to the untreated control with no comparison to either drug alone (38). The in vivo effect of the drug combination was not investigated in this study.…”
Section: Discussionmentioning
confidence: 90%
“…A recent retrospective case-control study in Mediterranean men undergoing a prostate biopsy reported the use of the combination of aspirin and statins resulted in significantly less men diagnosed with prostate cancer compared to the untreated group (p<0001) (38). The investigators also evaluated the in vitro effects of aspirin, simvastatin and the combination in LNCaP and PC3 cells.…”
Section: Discussionmentioning
confidence: 99%
“…The dose of aspirin is varied depend on different diseases, such as 75-325 mg/day for cardiovascular disease, ≤325 mg/day for osteoarthritis and rheumatoid arthritis, and low dose of 75-300 mg/day for colorectal cancer and endometrial cancer (8,31-33). In addition, in vitro experiments, the effective doses of aspirin in most studies in colon, prostate or breast cancer cells vary from 1-10 mmol/l (26,34,35). our data suggested that the IC 50 value of aspirin for cell growth inhibition was 4.23 mmol/l.…”
Section: Discussionmentioning
confidence: 60%
“…When combined with statins in treatment, aspirin was shown to decrease proliferation of LNCaP cells with a reduction in cyclin D1 levels—which modulates cell cycle progression (Olivan et al, 2015). Aspirin, on its own, was shown to cause ubiquitin-dependent degradation of cyclin D1 in colorectral cancer cells (Thoms et al, 2007).…”
Section: Aspirin and Cox-independent Regulation Of The Cell Cycle In mentioning
confidence: 99%